Exploration of the Spiritual Expectations of Patients in a Swiss Hemodialysis Center - Simon Mastrangelo; Etienne Rochat; Menno Pruijm (Kidney and Dialysis)
Background: Whether hemodialysis patients want caregivers to discuss spirituality is poorly studied, especially in Europe. The goal of this qualitative study was to explore the spirituality and spiritual expectations of hemodialysis patients in a Swiss dialysis center. Methods: Semi-structured, qualitative interviews were performed by an experienced sociologist with dialysis patients in the ambulatory dialysis unit of the University Hospital of Lausanne. The interviews included a set of open questions on the role that spirituality plays in patients’ lives, in coping with their illness and in the recent COVID-19 epidemic. All interviews were recorded, transcribed, coded and analyzed following the approach of content analysis. Findings: Twenty interviews were performed in 2022. In total, 14/20 patients practiced some form of religion (believers), four were agnostics, and two defined themselves as atheist. The majority (15/20) confirmed that spirituality plays a positive role to preserve hope and to manage the difficulties caused by the disease and its treatment; one out of four wishes to discuss spirituality in the hospital setting. The largest needs are related to social dimensions (isolation, loneliness, need to talk, financial problems). Their level of spirituality has not been impacted by the COVID-19 pandemic. Discussion: In this pilot study, spirituality in a broad sense was important for the majority of the patients, and a quarter of them would like it to be actively addressed by healthcare professionals. They also ask for more attention to social and socio-economic difficulties.